Employee Benefits and Job Satisfaction in Faith Based Institutions in Uganda - Rukanyangira, Nazarious; Kitata, Nassolo Belinda; Kitata, Paul William (European Journal of Human Resource, 2023)
Purpose: The study was conducted on the influence of employee benefits on job satisfaction in Faith Based Institutions in Uganda, a case study of the Church of Uganda¸ Provincial Secretariat. The study was guided by specific objectives as; to establish the influence of health insurance, to examine the effect staff allowances, and to establish the relationship between retirement benefits and job satisfaction at Church of Uganda¸ Provincial Secretariat. Materials and Methods: The study used a blend of cross sectional¸ descriptive, and correlation research designs, with questionnaires and interviews as data collection methods. A sample size of 92 was attained from a study population of 130 employees. Findings: Findings revealed no relationship between health benefits and job satisfaction (r=-0.001 Sig = p = 0.990 â‰¥ 0.05); a weak positive relationship between staff allowances and job satisfaction (r = 0.253** Sig=0.015> 0.01) and adjusted R-Square value of 0.053; a weak positive relationship between staff allowances and job satisfaction (r = 0.260** Sig=0.012> 0.05) and adjusted R-Square value of 0.057; Basing on the findings there is no relationship between health benefits and job satisfaction while weak relationships exists between staff allowances¸ retirement benefits and job satisfaction. Implications to Theory, Practice and Policy: The COU Provincial Secretariat need to put into place health benefit system and improve both allowance and retirement benefits so that both may make bigger contribution to job satisfaction.